2008
DOI: 10.1103/physrevb.77.104421
|View full text |Cite
|
Sign up to set email alerts
|

Absorption suppression in photonic crystals

Abstract: Abstract. We study electromagnetic properties of periodic composite structures, such as photonic crystals, involving lossy components. We show that in many cases a properly designed periodic structure can dramatically suppress the losses associated with the absorptive component, while preserving or even enhancing its useful functionality. As an example, we consider magnetic photonic crystals, in which the lossy magnetic component provides nonreciprocal Faraday rotation. We show that the electromagnetic losses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Such a gain medium is provided by a periodic structure supporting a DBE as we demonstrate here for a specific example based on some preliminary ideas expressed in [48]. To understand origins of the giant gain let us recall some basic properties of DBE in photonic crystals.…”
Section: Background and Methodsmentioning
confidence: 99%
“…Such a gain medium is provided by a periodic structure supporting a DBE as we demonstrate here for a specific example based on some preliminary ideas expressed in [48]. To understand origins of the giant gain let us recall some basic properties of DBE in photonic crystals.…”
Section: Background and Methodsmentioning
confidence: 99%
“…3, it was theoretically shown that the spatial distribution of the electric field in a MPC strongly depends on both the field frequency and the material parameters of magnetic and non-magnetic layers. As a result, a possibility of a substantial enhancement of the Faraday effect as well as nonlinear magneto-optical effects in MPCs was predicted [3][4][5] and experimentally verified. 4 The dependence of optical and magneto-optical properties of PCs on the spatial distribution of electromagnetic waves inside PCs can be considered as an optical analog of the Borrmann effect, which manifests itself in anomalous absorption/transmission of x-rays in near-perfect crystals.…”
Section: Introductionmentioning
confidence: 99%
“…An important and guiding example of a two-component dielectric medium composed of a high-loss and lossless components was constructed in [FigVit8]. The example was a simple layered structure which had magnetic properties comparable with a natural bulk material but with 100 times lesser losses in a wide frequency range.…”
Section: Introductionmentioning
confidence: 99%